The Effectiveness of the Logic Evaluation Model in K-13 Curriculum Analysis - Mexdadoris, Mexdadoris; Jama, Jalius (LPPM Undiksha, 2020)
This study aimed to evaluate the implementation of the curriculum using the Logic Evaluation Model which includes 4 aspects; input evaluation, activity evaluation, output evaluation and outcome evaluation. The study approach used was mixed approach with a sequential explanatory method (sequence of evidence). This study was conducted by doing quantitative research first, then continue the research with qualitative methods to find conclusions. The sampling technique used Henry King's Nomogram Table, so that the number of teachers involved in this study was 78. In this study, researchers found that the implementation of Kurikulum 2013 was still quite sufficient with an average score was 3.84 and the TCR was 75.52%. The results of the evaluation of Kurikulum 2013 implementation on the input aspect was good with an average score was 3.96 and the TCR was 80.28%, in activity aspect it is sufficient with 3.70 average score and the TCR was 74.06%, The output aspect of Kurikulum 2013 implementation is sufficient with the average TCR was 3.96 and the average indicator was 73.62%, then the outcomes aspect is sufficient with the average score was 3.73 and the TCR was 74.13%. This research implies that there is a need for improvement in activities, inputs, and outcomes aspect, even though the activity evaluation component showed good Kurikulum 2013 implementation.